Effect of exogenous supplementation of GnRH or hCG on fertility in Kenguri ewes - SAJJAN, LEENA; HONNAPPAGOL, SURESH S; TANDLE, M K; DILIPKUMAR, DILIPKUMAR; APPANNAVAR, M M; NADOOR, PRAKASH (The Indian Journal of Animal Sciences, 2014)
The estimation of steroid hormone profile at different days of estrous cycle is indicative of the ovarian status of the animal. The administration of hCG on day 0 of estrous cycle and day 12 of post mating improved lambing percentage and also fertility. Among the 2 exogenous hormonal supplementations hCG therapy on day 0 and day 12 of post mating appeared to be the best in improving fertility in Kenguri ewes. The hormonal therapies are cost effective and are of great economic benefit to the farmers involving in sheep rearing.